Strategi Pengembangan Usahatani Bawang Merah di Kecamatan Simpang Simpang Tiga Kabupaten Pidie - Edy Marsudi; Cut Nadara Elakadana; Fajri (Departemen Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala associated with AAI (Asosiasi Agribisnis Indonesia). Jl. Tgk. Hasan Krueng Kalee No. 3, Kopelma Darussalam, Banda Aceh, 23111, Indonesia. Email: agrisep@usk.ac.id, 2026)
Shallots represent a vital agricultural commodity for households and the food industry, supported by strong domestic and export demand. Simpang Tiga Subdistrict in Pidie Regency, Aceh, serves as a key production center with considerable potential for shallot farming development. Nevertheless, farmers continue to face structural and environmental challenges, including the absence of proper storage facilities and recurring pest and disease outbreaks. This study aims to identify internal and external factors influencing shallot farming, determine the strategic position using SWOT analysis, formulate development strategies, and prioritize them through the Quantitative Strategic Planning Matrix (QSPM). Data were collected through observation and in-depth interviews with purposively selected farmers, agricultural extension officers, and officials from the Department of Agriculture. The analysis utilized the Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, SWOT matrix, and QSPM. The findings reveal that the primary strength is farmers' experience (score = 0.562), while the most significant weakness is the seasonal nature of planting (score = 0.209). The main opportunity is the subdistrict's status as a shallot production hub (score = 0.436), and the greatest threat is pest and disease infestations (score = 0.276). The strategic position falls within Quadrant I, suggesting the adoption of an aggressive growth strategy. Based on the QSPM, the highest-priority strategy is optimizing government support and technology to enhance cost efficiency and productivity, with a Total Attractiveness Score (TAS) of 6.696. These findings underscore the need for integrated, sustainable strategies to enhance the competitiveness and resilience of shallot farming in Simpang Tiga.